A special issue of Essays in Biochemistry on current educational developments in molecular bioscience. Issue 1 (29th April 2022) - Mello, Luciane V.; Watson, Helen R.
Abstract: The 4th joint UK Biochemical Society and Federation of European Biochemical Societies (FEBS) education event, 'Evolving Molecular Bioscience Education' took place online on May 27 and 28, 2021. The event, continuing the biennial series, comprised the invited speakers' talks, group discussions and other participants' pre-recorded flash presentations. Although the UK dominated, there were also speakers and participants from other European countries and other continents. This special issue includes a varied collection of articles written by the speakers and other participants.